2016
DOI: 10.1002/acr.22787
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Fatigue in Rheumatoid Arthritis Patients in Remission or in a Low Disease Activity State

Abstract: ObjectiveFatigue is a frequently occurring symptom in patients with rheumatoid arthritis (RA). Our aims were to assess the level of reported fatigue in RA patients who had achieved remission or low disease activity after 6 months of treatment with disease‐modifying antirheumatic drugs (DMARDs), and to explore associations between fatigue and demographics, disease activity, and other patient‐reported outcomes in this patient group.MethodsA total of 2,193 RA patients (ages ≥18 years) starting either methotrexate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 16 publications
4
39
2
1
Order By: Relevance
“…The low level of improvement in SF-36 MCS is likely because, consistent with previous findings [30,33], SF-36 MCS scores were close to normal at baseline; hence, there was limited scope for improvement. Other studies have also found that patients achieving remission or LDA have residual symptoms as determined by PROs assessing pain, disability, fatigue, and global disease activity [17][18][19]. Taken together, our findings and those from other studies indicate that, despite achieving remission (assessed by composite measures of disease activity), some patients with RA still have residual symptoms.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The low level of improvement in SF-36 MCS is likely because, consistent with previous findings [30,33], SF-36 MCS scores were close to normal at baseline; hence, there was limited scope for improvement. Other studies have also found that patients achieving remission or LDA have residual symptoms as determined by PROs assessing pain, disability, fatigue, and global disease activity [17][18][19]. Taken together, our findings and those from other studies indicate that, despite achieving remission (assessed by composite measures of disease activity), some patients with RA still have residual symptoms.…”
Section: Discussionsupporting
confidence: 80%
“…Norwegian and North American registry studies of patients have also provided evidence of residual symptoms. In Norway, $30% of patients starting new disease-modifying antirheumatic drug (DMARD) therapy who achieved remission (DAS28) after 6 months reported high levels of fatigue (VAS) [18]. In North America, 57-76% of patients starting biologic therapy who achieved lower disease activity [86% LDA or remission (CDAI)] after 12-15 months did not achieve the minimum clinically important difference (MCID) for various PROs {physical function [modified Health Assessment Questionnaire (HAQ): 76%], pain (VAS: 58%), fatigue (VAS: 57%), and patient's assessment of disease activity [Patient's Global Assessment of Disease Activity (PtGA)]: 57%} [19].…”
Section: Introductionmentioning
confidence: 99%
“…Virtually all treatments in RA will reduce fatigue, including conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs), targeted synthetic DMARDs, biologic DMARDs and corticosteroids. 37 39–54 The average effect of treatment on fatigue in active RA with various advanced therapies is meaningful but not large. 39 Treatment of disease activity in RA has a small impact on fatigue, whereas physical inactivity, poor sleep and depressed mood explain most of the fatigue.…”
Section: Treatmentmentioning
confidence: 99%
“…However, the participants were recruited consecutively and were all in need of their first biologic treatment, and had no major comorbidities. The patients in the study live along the west coast of Norway, but we assume the selection is not very different from the majority of RA patients living in other parts of Norway (Brinkmann et al, 2018, Olsen et al, 2016.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%